Gastro Retentive Drug Delivery Systems (Grdds)- Comprehensive Review - Martin, S.; Sundaram, I. Soma (Journal of Neonatal Surgery, 2025)
Gastrointestinal transit time is a critical factor in the pharmacokinetics of many orally administered drugs. Conventional oral formulations often fail to maintain adequate plasma drug levels for extended periods, particularly for drugs with a narrow absorption window, poor solubility at higher pH, or those that are unstable in intestinal environments. GRDDS are specially engineered to address these limitations by remaining in the stomach for prolonged periods, thus ensuring consistent drug release and improved systemic absorption. Various technological strategies have been developed to achieve gastro retention, including floating systems that maintain buoyancy in gastric fluids, mucoadhesive formulations that bind to the stomach lining, expandable systems that resist gastric emptying by increasing in size, and high-density systems that sink and settle in the stomach. These systems must be optimized based on physiological parameters such as gastric pH, motility, and the presence of food, which can significantly affect their performance and therapeutic outcomes. Recent advancements in materials science, nanotechnology, and pharmaceutical engineering have led to the development of next-generation GRDDS with enhanced functionalities, such as targeted drug release, environmental responsiveness, and improved patient compliance. The integration of 3D printing technologies and intelligent polymers offers further potential for the personalization of GRDDS. This review critically examines these innovations and their implications for the future of oral drug delivery.